(untitled) (Eurasian Scientific Herald, 2024)
Currently, primary attention should be paid to the personality of the coach, as they are the key figure in athlete training. This article provides insights into the professional responsibilities of a coach-teacher. Additionally, it emphasizes the principles of possessing sufficient experience and knowledge required by the coach.